Phenolic Composition, in vitro Antioxidant and Anticancer Activities of Hypericum Japonicum Thunb and Scoparia Dulcis L - Quang-Ung Le *; Horng-Liang Lay; Ming- Chang Wu (Lorestan University of Medical Sciences, 2019)
Background and Aim: Hypericum Japonicum Thunb (HT) and Scoparia Dulcis L (SL) have received considerable attention as natural products for their applications with health benefits. This study aimed at investigating the in vitro antioxidant and HepG2 (human liver cancer cell line) and A549 (adenocarcinomic human alveolar basal epithelial cell line) growth inhibitory effect of the ethanol extracts from the HT and SL. Materials and Methods: Total phenolic and flavonoid contents were identified. Antioxidant activity was determined by measuring hydroxyl radical scavenging activity, 2,2'-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid) (ABTS+) and 2,2'-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activities. Phenolic compounds were identified by high performance liquid chromatography (HPLC) method. The activity of the apoptotic factors Bcl-2, Bad, Bax, Caspase-3 and Caspase-9 were measured by Western blotting. Results: The chlorogenic acid and rosmarinic acid were the compounds that had been identified in the HT. The rutin and rosmarinic acid were newly identified compounds from the SL. Moreover, it was found that the higher levels of ABTS+, DPPH and hydroxyl radical scavenging activities were detected from the HT extract with IC50 of 45.13±0.89, 89.29±0.78 and 38.32±0.17µg/mL, respectively. The HT and SL extracts could induce HepG2 growth inhibition with IC50: respectively 245.755 ± 2.23b µg/mL and 553.32 ± 14.46a µg/mL and also induce A549 growth inhibition with IC50 of the HT and SL: 314.15± 5.96b µg/mL and 446.35± 0.9a µg/mL at 48 hr, respectively. The HT and SL extracts stimulated the apoptotic factors including bcl-2, bad, caspase-3, caspase-9 in HepG2; p53, caspase-3, bax and bad in A549. Conclusion: The findings strongly suggest that the HT and SL extracts could be an excellent sources of antioxidants as functional food ingredients in the prevention and treatment of cancer.